Antimicrobial Resistance and Molecular Characterization of Citrobacter spp. Causing Extraintestinal Infections - Liu, Liyun; Zhang, Ling; Zhou, Haijian; Yuan, Min; Hu, Dalong; Wang, Yonglu; Sun, Hui; Xu, Jianguo; Lan, Ruiting (Frontiers in Cellular and Infection Microbiology, 2021)
Objectives This prospective study was carried out to investigate molecular characteristics and antimicrobial susceptibility patterns of Citrobacter spp. from extraintestinal infections. Methods Forty-six clinical Citrobacter spp. isolates were isolated from hospital patients with extraintestinal infections and analyzed by multilocus sequence typing (MLST) using seven housekeeping genes. Antimicrobial susceptibility testing was performed by disk diffusion method according to the Clinical and Laboratory Standards Institute (CLSI) recommendations. Adhesion and cytotoxicity to HEp-2 cells were assessed. Results The 46 clinical Citrobacter spp. isolates were typed into 38 sequence types (STs), 9 of which belonged to four clonal complexes (CCs). None of the isolates shared the same ST or CCs with isolates from other countries or from other parts of China. Over half of the isolates were multidrug-resistant (MDR), with 17/26 C. freundii, 5/6 C. braakii, and 3/14 C. koseri isolates being MDR. Moreover, four isolates were carbapenem resistant with resistance to imipenem or meropenem. Among eight quinolone resistant C. freundii, all had a mutation in codon 59 (Thr59Ile) in quinolone resistance determining region of the gyrA gene. Only a small proportion of the isolates were found to be highly cytotoxic and adhesive with no correlation to sample sources. Conclusions There was a diverse range of Citrobacter isolates causing extraintestinal infections and a high prevalence of MDR.